State and development of the education market of higher education in Kazakhstan (Journal of Economic Research & Business Administration, 2015)
This article considers and characterizes the stages of the development of the educational services market and analyzes the current state of the national system of higher education. A descriptive and comparative analysis of the causes and effects has been applied in the research; historical, functional, systemic and sociological approaches have been used. The article considers key issues in the reform of the higher education system, with a detailed description of all stages of the reforms in the period since 1991 to the present. In order to form a national model, able to provide high quality training, competitive in the world educational space, enabling to move from primary economy to knowledge economy, it is necessaryto ensure and increase the competitiveness of the entire system of higher education.
Keywords: financing; higher education; market of educational services; reform; integration; continuous education